Faktor-Faktor Penyebab Lemahnya Penegakan Hukum Pemilu di Indonesia - Bakry, Umar Suryadi (JUSTICE: Journal of Social and Political Science, 2026)
General elections (Pemilu) are the primarily instrument in Indonesia's democracy system  as a means of implementing popular sovereignty as mandated by the 1945 Constitution of the Republic of Indonesia. Therefore, the existence of election election law plays strategic role in ensuring the implementation of democratic, honest, fair, and integrity-based elections. This article aimed to analyze the legal framework for election in Indonesia and examine various forms of violations and problem in enforcing election law in practice. The research method used is qualitative descriptive approach with secondary data analysis sourced from law and regulations, Constitutional Court decisions, Election Supervisory Agency (Bawaslu) Reports, and research and survey results from related institutions. The results of the study indicate that normatively Indonesia has a relatively comprehensive legal framework, starting from the 1945 Constitution, the Election and Regional Election Laws, the General Election Commission (KPU) Regulations, and Constitutional Court decisions. However, at the empirical level, high levels of election violations are still found, especially violations of the code of ethics of elections organizers, administrative violations, money politics, and lack of neutrality of state officials.